Double-layer solid electrolyte, all-solid-state lithium battery and preparation method of all-solid-state lithium battery

By using the design of a double-layer solid electrolyte and a lithium nitrogen compound intermediate layer in lithium-ion batteries, the problems of lithium dendrites formation and interface instability are solved, and the circulation performance and safety of lithium-ion batteries are significantly improved.

CN119695259APending Publication Date: 2025-03-25HUNAN LIFANG NEW ENERGY SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411830832.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the interface instability between the solid electrolyte and the positive and negative electrodes is problematic, resulting in the formation of lithium dendrites, decreased cycle life and safety problems.

Method used

A double-layer solid electrolyte, including sulfide-based electrolyte and chloride-based electrolyte, is adopted to promote uniform and rapid transmission of lithium ions through the structural design of yLiMO3·Dn+Cln, avoid the formation of lithium dendrites, and use lithium nitrogen compounds as an intermediate layer to inhibit the interface reaction between the sulfide-based electrolyte and lithium metal.

Benefits of technology

The circulation performance and energy density of all solid-state lithium batteries have been significantly improved, with the energy density not less than 350Wh/kg, the capacity retention rate after 100 weeks of circulation is not less than 90%, and the safety is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695259A_ABST
    Figure CN119695259A_ABST
Patent Text Reader

Abstract

The invention discloses a double-layer solid electrolyte, an all-solid-state lithium battery and a preparation method thereof. The double-layer solid electrolyte comprises a sulfide-based electrolyte and a chloride-based electrolyte; the chloride-based electrolyte is yLiMO3. Dn + Cln, in the formula, M is at least one of Nb and Ta, y is more than or equal to 0.5 and less than or equal to 1.5, D is at least one of Ta, Hf and La, and n is the valence of the element D. LiMO3 in the chloride-based electrolyte can generate a piezoelectric effect in the charging and discharging process, uniform and rapid transmission of lithium ions can be promoted, the interface stability of metal lithium and the sulfide-based electrolyte can be improved, lithium dendrites are inhibited, and the prepared all-solid-state lithium battery has relatively good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state lithium batteries, and specifically relates to a double-layer solid electrolyte, an all-solid-state lithium battery and a preparation method thereof. Background Art

[0002] With the advancement of the national "carbon peak, carbon neutrality" strategy, an energy revolution has been launched in the transportation field, and the popularization of electric vehicles has been rapidly promoted. Among automotive power batteries, lithium-ion batteries currently dominate. However, lithium-ion batteries generally use flammable liquid ester organic electrolytes, which pose safety hazards and lead to frequent safety accidents. An effective way to solve safety problems is to use solid electrolytes instead of organic liquid electrolytes. However, there is an interface instability problem between solid electrolytes and positive and negative electrodes, and its side reactions lead to large interface resistance, which is not conducive to interfacial charge transfer, causing large battery polarization and rapid performance degradation. Different solid electrolytes have different electrochemical windows, and the electrochemical window of a single solid electrolyte is often relatively narrow, which cannot simultaneously meet the low voltage resistance problem of the negative electrode and the high voltage resistance problem of the positive electrode.

[0003] The prior art CN118630300A and CN117199330A disclose that the interface problem between the solid electrolyte and the positive and negative electrodes is solved by using a reduction-resistant sulfide-based solid electrolyte on the negative electrode side and an oxidation-resistant halide-based solid electrolyte on the positive electrode side. However, when faced with a lithium negative electrode with stronger reducibility and a positive electrode with a higher operating voltage, such as lithium-rich manganese-based materials and high-voltage lithium cobalt oxide, the positive and negative electrodes still face interface stability problems and lithium dendrite problems, resulting in a decreased cycle life and safety issues. Summary of the invention

[0004] The purpose of the present invention is to provide a double-layer solid electrolyte to overcome the problem of lithium dendrites existing in the above-mentioned prior art when using a lithium negative electrode or a positive electrode with a high working voltage, which leads to the defects or shortcomings of reduced cycle life.

[0005] Another object of the present invention is to provide an all-solid-state lithium battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A double-layer solid electrolyte, comprising a sulfide-based electrolyte and a chloride-based electrolyte;

[0008] The chloride-based electrolyte is yLiMO3·D n+ Cl n , wherein M is at least one of Nb and Ta, 0.5≤y≤1.5, D is at least one of Ta, Hf and La, and n is the valence of the D element.

[0009] The present invention provides a double-layer solid electrolyte, comprising a sulfide-based electrolyte and a chloride-based electrolyte; yLiMO3·D n+ Cl n The LiMO3 in the battery can produce a piezoelectric effect during the charge and discharge process, which can promote the uniform and rapid transmission of lithium ions and avoid the formation of lithium dendrites. LiMO3 produces a piezoelectric effect and has a certain rigidity. When pressurized, it has good contact with the sulfide-based electrolyte, which is beneficial to the transmission of lithium ions. The sulfide-based electrolyte and the chloride-based electrolyte can work together to take into account the stability of the positive and negative electrode interfaces, and can change the direction of dendrite growth, prevent the formation of continuous lithium dendrites, and inhibit battery short circuits and safety issues caused by dendrites.

[0010] It should be noted that the yLiMO3·D n+ Cl n , 0.5≤y≤1.5, for example but not limited to, y is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5, or a range between any of the above values.

[0011] In some preferred embodiments, the yLiMO3·D n+ Cl n It can be achieved by LiMO3 and D n+ Cl n Made by ball milling.

[0012] Specifically, the rotation speed of the ball mill is 300-600 rpm.

[0013] Specifically, the ball milling is performed in an inert gas.

[0014] Specifically, the ball milling time is 5 to 20 hours.

[0015] Furthermore, the sulfide-based electrolyte is Li 6-x PS 5-x A 1+x , wherein A is at least one of Cl and Br, and 0≤x≤0.8. Within this range, the rapid transport of lithium ions and the suppression of lithium dendrites can be further promoted.

[0016] In some preferred embodiments, the Li 6-x PS 5-x A 1+x LiCl, LiBr, Li2S and P2S5 were prepared by ball milling combined with heat treatment.

[0017] Specifically, the ball milling is performed in an inert gas.

[0018] Specifically, the rotation speed of the ball mill is 300-600 rpm.

[0019] Specifically, the ball milling time is 5 to 20 hours.

[0020] Specifically, the heat treatment temperature is 450-550° C., and the heat treatment time is 4-20 hours.

[0021] Furthermore, the Li 6-x PS 5-x A 1+x The ionic conductivity is 5×10 -3 S / cm~3×10 -2 S / cm. Within this range, the rapid transport of lithium ions and the suppression of lithium dendrites can be more effectively promoted.

[0022] The present invention also provides an all-solid-state lithium battery, comprising the above-mentioned double-layer solid electrolyte.

[0023] Furthermore, it also includes a lithium negative electrode, an intermediate layer and a positive electrode; the intermediate layer is a lithium nitrogen compound.

[0024] Furthermore, the lithium nitrogen compound is Li 3-x T x N, wherein T is at least one of Ni, Cu, Co, Mg, Zn and Fe, wherein 0.2≤x≤0.6. Li 3-x T x The presence of N can effectively inhibit the interfacial reaction between sulfide-based solid electrolytes and lithium metal and promote the 3-x T x The uniform deposition and stripping of N on the inner surface inhibits the formation of lithium dendrites in sulfide solid electrolytes. 3-x T x N can promote the lithium metal 3-x T x The uniform deposition and stripping of N on the inner surface inhibits lithium dendrites.

[0025] Specifically, the lithium nitrogen compound is prepared by ball milling Li3N and metal T powder.

[0026] Specifically, the rotation speed of the ball mill is 300-600 rpm.

[0027] Specifically, the ball milling time is 5 to 20 hours.

[0028] Specifically, the ball milling is performed in an inert gas.

[0029] Specifically, the average particle size of the lithium nitrogen compound is 100 to 500 nm.

[0030] Furthermore, the thickness of the chloride-based electrolyte in the double-layer solid electrolyte is 10 to 100 μm. Within this range, the lithium ion transport performance, mechanical strength, and battery energy density can be better balanced, and the growth of lithium dendrites can be effectively inhibited.

[0031] Furthermore, the layer thickness of the sulfide-based electrolyte in the double-layer solid electrolyte is 10 to 100 μm. Within this range, the lithium ion transport performance, mechanical strength, and battery energy density can be better balanced, and the growth of lithium dendrites can be effectively inhibited.

[0032] Furthermore, the layer thickness ratio of the sulfide-based electrolyte and the chloride-based electrolyte in the double-layer solid electrolyte is (1-20):1.

[0033] Furthermore, the thickness of the intermediate layer is 1 to 10 μm. Within this range, the reaction between metallic lithium and sulfide-based electrolyte can be more effectively suppressed, the formation of lithium dendrites can be suppressed, and the cycle life and energy density of the battery can be better balanced.

[0034] The present invention also provides a method for preparing the above-mentioned all-solid-state lithium battery, comprising the following steps:

[0035] S1. The intermediate layer is evenly dispersed on the surface of the lithium negative electrode, and the surface-modified lithium negative electrode is obtained after rolling;

[0036] The sulfide-based electrolyte and the binder are mixed evenly by dry method and rolled to obtain a sulfide-based electrolyte membrane; the chloride-based electrolyte and the binder are mixed evenly by dry method and rolled to obtain a chloride-based electrolyte membrane;

[0037] The positive electrode active material, the binder, the conductive agent and the solid electrolyte are mixed evenly by dry method and rolled to obtain the positive electrode film;

[0038] S2. The positive electrode membrane, chloride-based electrolyte membrane, sulfide-based electrolyte membrane, and surface-modified lithium negative electrode are pressed in sequence, and aluminum foil and copper foil are placed on the positive and negative electrode sides respectively to obtain an all-solid-state lithium battery.

[0039] Specifically, the sulfide-based electrolyte is pressed onto the middle layer of the surface-modified lithium negative electrode.

[0040] The adhesive in the present invention can be selected from commonly used adhesives, such as but not limited to one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or polyperfluoroethylenepropylene.

[0041] In some preferred embodiments, the adhesive is polytetrafluoroethylene, which can be fiberized by shear force during the mixing process to form a three-dimensional link network, which is more conducive to film formation.

[0042] The conductive agent in the present invention can be selected from commonly used conductive agents, such as but not limited to one or more of acetylene black, SuperP, nanocarbon tubes or nanocarbon fibers.

[0043] In some preferred specific embodiments, the positive electrode active material includes one or more of spinel lithium manganese oxide, spinel nickel lithium manganese oxide, lithium manganese phosphate, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt phosphate, lithium vanadium phosphate, lithium cobalt oxide, nickel cobalt aluminum-based layered material, nickel cobalt manganese-based layered material or lithium-rich manganese-based layered material.

[0044] Furthermore, the solid electrolyte in step S1 is a chloride-based electrolyte B.

[0045] Furthermore, the chloride-based electrolyte B and the chloride-based electrolyte have the same composition.

[0046] In some preferred embodiments, the mass ratio of the positive electrode active material, the binder, the conductive agent, and the solid electrolyte is (70-90): (0.1-5): (1-10): (1-20).

[0047] Specifically, the thickness of the positive electrode film is 50-200 μm.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The present invention provides a double-layer solid electrolyte, including a sulfide-based electrolyte and a chloride-based electrolyte with a special structure, which can effectively promote the uniform and rapid transmission of lithium ions, effectively inhibit the interface reaction and lithium dendrite growth to avoid the formation of lithium dendrites; by preparing a full-solid-state lithium battery with the double-layer solid electrolyte and combining the lithium nitrogen compound as an intermediate layer, the interface reaction between the sulfide-based solid electrolyte and lithium metal can be effectively inhibited, and the lithium metal can be promoted in the Li 3-x T x The uniform deposition and stripping of N on the inner surface inhibits the generation of lithium dendrites in the sulfide solid electrolyte; the cycle performance and energy density of the prepared all-solid-state lithium battery are significantly increased, the energy density is not less than 350Wh / kg, the capacity retention rate is not less than 90% after 100 cycles, and the safety is relatively high. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a schematic structural diagram of the all-solid-state lithium battery of the present invention;

[0051] Figure 2 The charge and discharge curve of the all-solid-state lithium battery prepared in Example 5;

[0052] Figure 3 This is a cycle life diagram of the all-solid-state lithium battery prepared in Example 5;

[0053] Figure 4 This is the cycle life diagram of the all-solid-state lithium battery prepared in Comparative Example 6. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0055] Example 1

[0056] A double-layer solid electrolyte, the double-layer solid electrolyte comprising a sulfide-based electrolyte and a chloride-based electrolyte; the sulfide-based electrolyte is Li 5.4 PS 4.4 ClBr 0.6 , the chloride-based electrolyte is 0.9LiNbO3·TaCl5;

[0057] Specifically, the Li 5.4 PS 4.4 ClBr 0.6 It is prepared by ball milling and heat treatment of LiCl, LiBr, Li2S and P2S5 in a nitrogen atmosphere, wherein the molar ratio of LiCl, LiBr, Li2S and P2S5 is 1:0.6:1.9:0.5; the ball milling time is 10 hours, the ball milling speed is 450rpm; the heat treatment temperature is 500°C; the heat treatment time is 10 hours;

[0058] The 0.9LiNbO3·TaCl5 is prepared by ball milling LiNbO3 and TaCl5 in a nitrogen atmosphere, wherein the molar ratio of LiNbO3 to TaCl5 is 0.9:1; the ball milling time is 10 hours, and the ball milling speed is 450 rpm.

[0059] Example 2

[0060] A double-layer solid electrolyte, the double-layer solid electrolyte comprising a sulfide-based electrolyte and a chloride-based electrolyte; the sulfide-based electrolyte is Li 5.5 PS 4.5 Cl 1.5 , the chloride-based electrolyte is 1.0LiTaO3·HfCl4;

[0061] Specifically, the Li 5.5 PS 4.5 Cl 1.5It is prepared by ball milling and heat treatment of LiCl, Li2S and P2S5 in a nitrogen atmosphere, wherein the molar ratio of LiCl, Li2S and P2S5 is 1.5:2:0.5; the ball milling time is 10 hours, the ball milling speed is 450rpm; the heat treatment temperature is 500℃; the heat treatment time is 10 hours;

[0062] The 1.0LiTaO3·HfCl4 is prepared by ball milling LiTaO3 and HfCl4 in a nitrogen atmosphere, wherein the molar ratio of LiTaO3 to HfCl5 is 1:1; the ball milling time is 10 hours, and the ball milling speed is 450 rpm.

[0063] Example 3

[0064] A double-layer solid electrolyte, the double-layer solid electrolyte comprising a sulfide-based electrolyte and a chloride-based electrolyte; the sulfide-based electrolyte is Li 5.5 PS 4.5 Cl 1.0 Br 0.5 , the chloride-based electrolyte is 0.5LiNbO3·LaCl3;

[0065] Specifically, the Li 5.5 PS 4.5 Cl 1.0 Br 0.5 It is prepared by ball milling and heat treatment of LiCl, LiBr, Li2S and P2S5 in a nitrogen atmosphere, wherein the molar ratio of LiCl, LiBr, Li2S and P2S5 is 1:0.5:2:0.5; the ball milling time is 10 hours, the ball milling speed is 450rpm; the heat treatment temperature is 500°C; the heat treatment time is 10 hours;

[0066] The 0.5LiNbO3·LaCl3 is prepared by ball milling LiNbO3 and LaCl3 in a nitrogen atmosphere, wherein the molar ratio of LiNbO3 to LaCl3 is 0.5:1; the ball milling time is 20 hours, and the ball milling speed is 600 rpm.

[0067] Example 4

[0068] A double-layer solid electrolyte, the double-layer solid electrolyte comprising a sulfide-based electrolyte and a chloride-based electrolyte; the sulfide-based electrolyte is Li 5.5 PS 4.5 Cl 0.8 Br 0.7 , the chloride-based electrolyte is 1.5LiTaO3·TaCl5;

[0069] Specifically, the Li 5.5PS 4.5 Cl 0.8 Br 0.7 It is prepared by ball milling and heat treatment of LiCl, LiBr, Li2S and P2S5 in a nitrogen atmosphere, wherein the molar ratio of LiCl, LiBr, Li2S and P2S5 is 0.8:0.7:2:0.5; the ball milling time is 10 hours, the ball milling speed is 450rpm; the heat treatment temperature is 500°C; the heat treatment time is 10 hours;

[0070] The 1.5LiTaO3·TaCl5 is prepared by ball milling LiTaO3 and TaCl5 in a nitrogen atmosphere, wherein the molar ratio of LiTaO3 to TaCl5 is 1.5:1; the ball milling time is 5 hours, and the ball milling speed is 350 rpm.

[0071] Comparative Example 1

[0072] The only difference from Example 1 is that only a sulfide-based electrolyte is contained.

[0073] Comparative Example 2

[0074] The only difference from Example 1 is that LiNbO3 is used to replace 0.9LiNbO3·TaCl5.

[0075] Comparative Example 3

[0076] The only difference from Example 1 is that 0.9LiNbO3·ZrCl4 is used instead of 0.9LiNbO3·TaCl5.

[0077] Comparative Example 4

[0078] The only difference from Example 1 is that 0.9LiSbO3·TaCl5 is used instead of 0.9LiNbO3·TaCl5.

[0079] Comparative Example 5

[0080] The only difference from Example 1 is that Li3InCl6 is used to replace 0.9LiNbO3·TaCl5.

[0081] Example 5

[0082] An all-solid-state lithium battery is prepared by the following preparation method:

[0083] S1. The sulfide-based electrolyte and polytetrafluoroethylene in Example 1 are mixed uniformly in a mass ratio of 100:2, and a sulfide-based electrolyte membrane (layer thickness of 30 μm) is obtained by shearing, dispersing, and rolling. The chloride-based electrolyte and polytetrafluoroethylene in Example 1 are mixed uniformly in a mass ratio of 100:2, and a chloride-based electrolyte membrane (layer thickness of 15 μm) is obtained by shearing, dispersing, and rolling.

[0084] Li 2.6 Cu 0.4 N is pressed on the surface of lithium metal foil, and the surface modified lithium anode (Li 2.6 Cu 0.4 N has a thickness of 5 μm, and the thickness of the metal lithium foil is 50 μm); the Li 2.6 Cu 0.4 N was prepared by ball milling Li3N and Cu with a molar ratio of 2.6:0.4 under a nitrogen atmosphere, the ball milling time was 10 hours, and the ball milling speed was 450 rpm;

[0085] LiNi 0.8 Co 0.1 Mn 0.1 O2 material, polytetrafluoroethylene, carbon nanotubes, and 0.9LiNbO3·TaCl5 were uniformly mixed in a weight ratio of 84:2:4:10, and a positive electrode film (thickness of 80 μm) was obtained by shear dispersion and roller pressing;

[0086] S2. The positive electrode film, the chloride-based electrolyte membrane, the sulfide-based electrolyte membrane, and the surface-modified lithium negative electrode are Figure 1 The structures shown are pressed in sequence, and aluminum foil and copper foil collectors are placed on the positive and negative sides respectively. After isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0087] Example 6

[0088] An all-solid-state lithium battery is prepared by the following preparation method:

[0089] S1. The sulfide-based electrolyte and polytetrafluoroethylene in Example 2 are uniformly mixed in a mass ratio of 100:2, and a sulfide-based electrolyte membrane (layer thickness of 40 μm) is obtained by shearing, dispersing, and rolling. The chloride-based electrolyte and polytetrafluoroethylene in Example 2 are uniformly mixed in a mass ratio of 100:2, and a chloride-based electrolyte membrane (layer thickness of 10 μm) is obtained by shearing, dispersing, and rolling.

[0090] Li 2.4 Ni 0.6 N is pressed on the surface of lithium metal foil, and the surface modified lithium anode (Li 2.4 Ni 0.6 N has a thickness of 4 μm, and the thickness of the metal lithium foil is 40 μm); the Li 2.4 Ni 0.6 N was prepared by ball milling Li3N and Ni with a molar ratio of 2.4:0.6 under a nitrogen atmosphere, the ball milling time was 10 hours, and the ball milling speed was 450 rpm;

[0091] LiCoO2 material, polytetrafluoroethylene, nanocarbon fiber, and 1.0LiTaO3·HfCl4 were uniformly mixed in a weight ratio of 82:1.5:4.5:12, and a positive electrode film (thickness of 100 μm) was obtained by shearing, dispersing, and rolling.

[0092] S2. The positive electrode film, the chloride-based electrolyte membrane, the sulfide-based electrolyte membrane, and the surface-modified lithium negative electrode are Figure 1 The structures shown are pressed in sequence, and aluminum foil and copper foil collectors are placed on the positive and negative electrodes respectively. After isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0093] Example 7

[0094] An all-solid-state lithium battery is prepared by the following preparation method:

[0095] S1. The sulfide-based electrolyte and polytetrafluoroethylene in Example 3 were mixed uniformly in a mass ratio of 100:1.5, and a sulfide-based electrolyte membrane (layer thickness of 35 μm) was obtained by shearing, dispersing, and rolling; the chloride-based electrolyte and polytetrafluoroethylene in Example 3 were mixed uniformly in a mass ratio of 100:1.5, and a chloride-based electrolyte membrane (layer thickness of 15 μm) was obtained by shearing, dispersing, and rolling;

[0096] Li 2.5 Co 0.5 N is pressed on the surface of metal lithium foil, and the surface modified lithium anode (Li 2.5 Co 0.5 N has a thickness of 5 μm, and the thickness of the metal lithium foil is 40 μm); the Li 2.5 Co 0.5 N was prepared by ball milling Li3N and Co with a molar ratio of 2.5:0.5 under a nitrogen atmosphere, the ball milling time was 10 hours, and the ball milling speed was 450 rpm;

[0097] Li 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2 material, polytetrafluoroethylene, nanocarbon fiber, and 0.5LiNbO3·LaCl3 were uniformly mixed in a weight ratio of 82.5:1.5:4.5:11.5, and a positive electrode film (thickness of 80 μm) was obtained by shear dispersion and roller pressing;

[0098] S2. The positive electrode film, the chloride-based electrolyte membrane, the sulfide-based electrolyte membrane, and the surface-modified lithium negative electrode are Figure 1 The structures shown are pressed in sequence, and aluminum foil and copper foil collectors are placed on the positive and negative electrodes respectively. After isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0099] Example 8

[0100] An all-solid-state lithium battery is prepared by the following preparation method:

[0101] S1. The sulfide-based electrolyte and polytetrafluoroethylene in Example 4 were mixed uniformly in a mass ratio of 100:2, and a sulfide-based electrolyte membrane (layer thickness of 45 μm) was obtained by shearing, dispersing, and rolling; the chloride-based electrolyte and polytetrafluoroethylene in Example 4 were mixed uniformly in a mass ratio of 100:2, and a chloride-based electrolyte membrane (layer thickness of 10 μm) was obtained by shearing, dispersing, and rolling;

[0102] Li 2.4 Co 0.6 N is pressed on the surface of metal lithium foil, and the surface modified lithium anode (Li 2.4 Co 0.6 N has a thickness of 6 μm, and the thickness of the metal lithium foil is 50 μm); the Li 2.4 Co 0.6 N was prepared by ball milling Li3N and Co with a molar ratio of 2.4:0.6 under a nitrogen atmosphere, the ball milling time was 10 hours, and the ball milling speed was 450 rpm;

[0103] LiNi 0.85 Co 0.1 Al 0.05 O2 material, polytetrafluoroethylene, carbon nanotubes, and 1.5LiTaO3·TaCl5 were uniformly mixed in a weight ratio of 83:1.5:4.5:11, and a positive electrode film (thickness of 100 μm) was obtained by shear dispersion and rolling.

[0104] S2. The positive electrode film, the chloride-based electrolyte membrane, the sulfide-based electrolyte membrane, and the surface-modified lithium negative electrode are Figure 1 The structures shown are pressed in sequence, and aluminum foil and copper foil collectors are placed on the positive and negative electrodes respectively. After isostatic pressing treatment, an all-solid-state lithium battery is obtained by packaging.

[0105] Comparative Example 6

[0106] The preparation method and steps are the same as those of Example 5, the only difference being that the solid electrolyte in Comparative Example 1 is used instead of the double-layer solid electrolyte in Example 1, that is, the all-solid-state lithium battery does not contain a chloride-based electrolyte membrane.

[0107] Comparative Example 7

[0108] The preparation method and steps are the same as those of Example 5, except that the double-layer solid electrolyte in Comparative Example 2 is used instead of the double-layer solid electrolyte in Example 1.

[0109] Comparative Example 8

[0110] The preparation method and steps are the same as those of Example 5, except that the double-layer solid electrolyte in Comparative Example 3 is used instead of the double-layer solid electrolyte in Example 1.

[0111] Comparative Example 9

[0112] The preparation method and steps are the same as those of Example 5, except that the double-layer solid electrolyte in Comparative Example 4 is used instead of the double-layer solid electrolyte in Example 1.

[0113] Comparative Example 10

[0114] The preparation method and steps are the same as those of Example 5, except that the double-layer solid electrolyte in Comparative Example 5 is used instead of the double-layer solid electrolyte in Example 1.

[0115] Comparative Example 11

[0116] The preparation method and steps are the same as those in Example 5, except that Li 2.6 Cu 0.4 N modifies the metallic lithium foil, that is, the all-solid-state lithium battery does not contain an intermediate layer.

[0117] Comparative Example 12

[0118] The preparation method and steps are the same as those in Example 5, except that Li3N is used instead of Li 2.6 Cu 0.4 N.

[0119] Performance Testing

[0120] 1. Test Method

[0121] (1) Capacity and energy density test: The all-solid-state lithium battery described in the above Example 5 and each comparative example was weighed m0, and charged and discharged at room temperature. It was charged to 4.2V at a constant current of 0.1C, and then discharged to 3V at a constant current of 0.1C (1C is defined as 200mA / g). The discharge capacity Q was recorded. 放 , Q 放 The integrated area in the range of 3 to 4.2 V is recorded as energy E, and the density energy density = E / m0;

[0122] (2) Capacity retention rate test: The all-solid-state lithium battery described in the above Example 5 and each comparative example was charged at room temperature at a constant current of 1C to 4.2V, then charged at a constant voltage at the same voltage to a cut-off current of 0.02C, and then discharged at a constant current of 1C to 3V, and the initial capacity Q0 was recorded. The cycle was repeated in this way. When the cycle reached 100 cycles, the capacity Q1 at this time was recorded, and the capacity retention rate (%) was calculated. Capacity retention rate (%) = Q1 / Q0 × 100%;

[0123] (3) Needle puncture test: The all-solid-state lithium battery described in the above Example 5 and each comparative example is charged at room temperature with a constant current of 1C to 4.2V, then charged at a constant voltage at this voltage to a cut-off current of 0.02C, then discharged at a constant current of 1C to 3V, and cycled for 3 weeks. Then, the all-solid-state battery is charged at a constant current of 1C to 4.2V and pierced with a nail. If it catches fire, it is rejected; if it does not catch fire, it is passed.

[0124] The test conditions in Example 6 are 3-4.5V, and 1C is defined as 200mA / g; the test conditions in Example 7 are 2.3-4.6V, and 1C is defined as 250mA / g; the test conditions in Example 8 are 3-4.3V, and 1C is defined as 200mA / g.

[0125] 2. Test results

[0126] The test results of various embodiments and comparative examples are shown in Table 1.

[0127] Table 1 Experimental results of various embodiments and comparative examples

[0128]

[0129] From Table 1 and Figures 2-3 It can be seen that the cycle performance of the all-solid-state lithium battery prepared by the double-layer solid electrolyte provided by the present invention is improved. The lithium negative electrode modified by lithium nitrogen compound combined with the double-layer solid electrolyte in the all-solid-state lithium battery further improves the cycle stability of the battery. After 100 cycles, the capacity retention rate is not less than 90%, the energy density is not less than 350Wh / kg, and the safety is relatively high, and the needle puncture test does not catch fire.

[0130] From Comparative Examples 6 to 10 and Figure 4 It can be seen from the figure that if a double-layer solid electrolyte is not used or other chloride-based electrolytes are used instead of the yLiMO3·D in the present invention, n+ Cl n The cycle stability of the prepared all-solid-state lithium battery is significantly reduced, and the energy density is significantly lower than that of the embodiment.

[0131] It can be seen from Comparative Examples 11 and 12 that if no intermediate layer is added to the all-solid-state lithium battery or other intermediate layers are used to replace the lithium nitrogen compound in the present invention, the cycle stability of the obtained all-solid-state lithium battery decreases.

[0132] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A double-layer solid electrolyte, characterized in that The double-layer solid electrolyte includes a sulfide-based electrolyte and a chloride-based electrolyte; The chloride-based electrolyte is yLiMO3·D n+ Cl n , wherein M is at least one of Nb and Ta, 0.5≤y≤1.5, D is at least one of Ta, Hf and La, and n is the valence of the D element.

2. The double-layer solid electrolyte according to claim 1, characterized in that: The sulfide-based electrolyte is Li 6-x PS 5- x A 1+x , wherein A is at least one of Cl and Br, and 0≤x≤0.

8.

3. An all-solid-state lithium battery, characterized in that: Comprising the double-layer solid electrolyte according to claim 1 or 2.

4. The all-solid-state lithium battery according to claim 3, characterized in that: It also includes a lithium negative electrode, an intermediate layer and a positive electrode; the intermediate layer is a lithium nitrogen compound.

5. The all-solid-state lithium battery according to claim 4, characterized in that: The lithium nitrogen compound is Li 3-x T x N, wherein T is at least one of Ni, Cu, Co, Mg, Zn and Fe, and 0.2≤x≤0.

6.

6. The all-solid-state lithium battery according to claim 3, characterized in that: The thickness of the chloride-based electrolyte in the double-layer solid electrolyte is 10 to 100 μm.

7. The all-solid-state lithium battery according to claim 3, characterized in that: The layer thickness of the sulfide-based electrolyte in the double-layer solid electrolyte is 10 to 100 μm.

8. The all-solid-state lithium battery according to claim 3, characterized in that: The layer thickness ratio of the sulfide-based electrolyte and the chloride-based electrolyte in the double-layer solid electrolyte is (1-20):

1.

9. The all-solid-state lithium battery according to claim 4, characterized in that: The thickness of the intermediate layer is 1-10 μm.

10. A method for preparing an all-solid-state lithium battery according to any one of claims 4 to 9, characterized in that: The steps include: S1. The intermediate layer is evenly dispersed on the surface of the lithium negative electrode, and the surface-modified lithium negative electrode is obtained after rolling; The sulfide-based electrolyte and the binder are mixed evenly by dry method and rolled to obtain a sulfide-based electrolyte membrane; the chloride-based electrolyte and the binder are mixed evenly by dry method and rolled to obtain a chloride-based electrolyte membrane; The positive electrode active material, the binder, the conductive agent and the solid electrolyte are mixed evenly by dry method and rolled to obtain the positive electrode film; S2. The positive electrode membrane, chloride-based electrolyte membrane, sulfide-based electrolyte membrane, and surface-modified lithium negative electrode are pressed in sequence, and aluminum foil and copper foil are placed on the positive and negative electrode sides respectively to obtain an all-solid-state lithium battery.

Citation Information

Patent Citations

  • Preparation method of silicon negative electrode for high-first-effect long-cycle all-solid-state battery

    CN117199330A

  • Solid electrolyte membrane, preparation method thereof and solid-state battery

    CN118630300A